A Production and operations management study on CKL Industries, Inc. - Santos, Rowell; Soriano, Erick Jon.; Tappa, Milette (Diliman, Quezon City College of Engineering, 1992)
A Production and Operations Management study was conducted on the production plant of CKL Industries, Inc., which dyes and finishes fabrics from textile weaving and knitting companies both locally in Cavite region and internationally in Asia. The study included documentation, evaluation and analyses of the facility's present production system, capacity planning, aggregate planning, and identification of possible improvement areas along with their corresponding recommendations. The study was focused on the dyeing section since this is found to be the limiting constraint of the service facility. The company is operating at 65.5% efficiency and 32.64% utilization, which translate to 51% capacity cushion, used by the company to meet fluctuations in demand. Analyses of the current system resulted in the identification of the following problem areas: Large reprocess rates encountered due to the shade being the subject to customers; specification. As large as 22.77% reprocess rate was experienced last year. The target rate of 8% was exceeded 10 out of 12 months. Large annual total inventory costs incurred due to inappropriate reorder point. Reorder point of 150 kilograms brought stock outs up to 465.22 kilograms amounting to P 34,891.82 incurred for the year 2002. Large operating costs due to inappropriate number of dyeing operators. Operating cost for the dyeing section composed mainly of salaries for the operators reached P 546,156.00.To address the problem areas, the implementation of the following recommendations were presented: (1) Investment in a spectrophotometer - an electronic device capable of accurately measuring color specifications in terms of intensity, hue, and value ti minimize discrepancy in the determination of shade. The alternative may allow the company to realize a saving of up to P 360,144.00 a year, an investment payback of 1.13 years; (2) Use the theoretical ROP of 244.46 kg - to ensure 95% service level. The alternative may allow the company to save P 7,147.95 per year; and (3) Maintain constant workforce level of 7 dyeing section operators be implemented. This scheme yielded the lowest annual cost across all alternatives considered. The alternative may allow the company to realize savings of up to P 35,763.67 per year.
IE 151
Feasibility study
Keywords: CKL industries; Fabric industry; Quality Control